Design of Microplate-Compatible Illumination Panels for a Semiautomated Benchtop Pipetting System. (August 2019) - Baillargeon, Pierre; Coss-Flores, Kervin; Singhera, Fakhar; Shumate, Justin; Williams, Hannah; DeLuca, Lina; Spicer, Timothy P.; Scampavia, Louis
Microplates are an essential tool used in laboratories for storing research materials and performing assays. Many types of laboratory automation exist that greatly reduce the effort needed to utilize microplates; however, there are cases where the use of such automation is not feasible or practical. In these instances, researchers must work in an environment where liquid handling operations are performed manually with handheld pipetting devices. This type of work is tedious and error-prone as it relies on researchers to manually track a significant amount of metadata, including transfer volumes, plate barcodes, well contents, and well locations. To address this challenge, we have developed an open-source, semiautomated benchtop system that facilitates manual pipetting using visual indicators. This device streamlines the process of identifying the location of wells so that the researcher can perform manual transfers in a more efficient, reliable, and accurate manner. This system utilizes a graphical user interface that allows the user to load worklists and then issues commands to illuminate wells of interest, providing a visual indicator for users to follow in real time. The software and hardware tools utilized for development, along with the implementation techniques used to produce this system, are described within.